Lennart's Innan Murarna Föll: Svenska kyrkan under kalla kriget [Before the Fall of the Walls: the Church of Sweden during the Cold War] - Book Review - Hjlem, Norman A. (Occasional papers on religion in Eastern Europe, 2019)
"This volume, like several others,1 is the product of historians, theologians, and churchpersons who, largely stimulated by the Finnish churchman Risto Lehtonen, have in recent years been exploring the role of and impact on churches of the Cold War, 1945-1989/90. The present work by Swedish scholars is unique in that Sweden was "non-aligned" during that time, and the Church of Sweden was (until 2000) a state church which did not enjoy the independence—political and otherwise—characteristic of churches in many other lands. This created a singular context for Sweden’s relation to the tensions and upheavals of the Cold War."